Tahapan dan Faktor yang Mempengaruhi Perkembangan Individu dalam Dunia Pendidikan: Stages and Factors that Influence Individual Development in the World of Education - Resqi Nabilah Rafiq (TARBIYAH: Jurnal Pendidikan dan Pembelajaran, 2025)
Understanding the stages of individual development is a crucial aspect of the success of the educational process. Learner development encompasses gradual changes in physical, cognitive, emotional, social, and moral domains from childhood to adulthood. This article provides a comprehensive discussion of developmental theories from key figures in educational psychology, such as Jean Piaget, Erik Erikson, Elizabeth B. Hurlock, and John W. Santrock, and their relevance to educational practice. The discussion emphasizes that each theory contributes significantly to understanding how learners think, form their identity, interact socially, and adapt to their environment. The findings indicate that the success of education is not determined solely by the delivery of academic content but also by the educator’s ability to tailor learning strategies to the developmental needs of learners. Collaboration among teachers, families, and the social environment plays a significant role in shaping learners into independent, characterful individuals capable of adapting to modern life.